ENTREPRENEURSHIP-ORIENTED PROJECT-BASED LEARNING TO IMPROVE STUDENTS' ENTREPRENEURSHIP ATTITUDES (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2021)
Science learning has potential in the nation's development efforts in terms of process. Applicative science materials can be used to develop the entrepreneurial spirit of students. However, the lack of student awareness in the application of science science has resulted in science education being only seen as science learning materials for junior high schools. Students lack the ability to have a scientific attitude that affects their entrepreneurial abilities. The purpose of this study is to determine the entrepreneurial ability of students by applying the PjBL learning model. This research is a quasi-experimental study with one group pretest-posttest design. The research population is the students of Science Education, Tidar University. Sampling by random method. The instrument used is a student entrepreneur response questionnaire. Data collection techniques through questionnaires. The results showed that the students' pretest results in the very low category were the highest at 43%. However, the posttest results showed progress with the highest percentage, namely the high category with a percentage of 38%. Thus, project-based learning (PjBL) has a good effect on students' interest in entrepreneurship